Solution for harvesting wave energy with Wells turbines and protection of the Black Sea coast - Budea Sanda; Simionescu Ștefan-Mugur; Florea George-Fabian (E3S Web of Conferences)
Harvesting the wave energy near coastline is useful to reduce romanian shoreline erosion but also to produce energy from renewable sources, useful for lighting the seafront. Two models of Wells turbines, with NACA 0010 and NACA 0021 blade profiles, were tested in the laboratory with air and water as working fluids, in two variants of operation – stand-alone rotor and with guide blades. Estimates and comparisons have been made regarding the energy that can be harvested using Wells turbines with 101 mm diameter rotors. Conclusions were drawn, such as that the Wells rotors show a better behavior in terms of energy produced when operating with a water column, with 7% better efficiency than with air. The Wells turbine with the NACA0021 blade profile performs better at air velocities above 4 m/s.